Marketing Management Analysis of CV Andhy Karya Products using Swot Method and Quantitative Strategic Planning Matrix (QSPM) - Ade Rizky Ramadhan; Ari Zaqi Faritsy (Takaza Innovatix Labs Ltd., 2026)
CV ANDHY KARYA is a metal casting and machinery company located in Klaten, Central Java, which experienced a decline in sales of palm oil machine spare parts and stove brackets during the period December 2023–February 2024. This study aims to identify internal and external factors affecting the company's marketing performance, formulate alternative marketing strategies, and determine the best strategic priority using SWOT analysis and the Quantitative Strategic Planning Matrix (QSPM). Data were collected through observation, interviews, and questionnaires distributed to 30 respondents. Data analysis used the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, IE matrix, SWOT matrix, and QSPM matrix. The analysis results showed that the total IFE score was 3.43 and EFE score was 2.10, placing CV ANDHY KARYA in quadrant IV of the IE matrix, a Growth and Build position. From eight alternative strategies formulated through SWOT analysis, the QSPM results indicated that the priority strategy is continuously developing product innovation and keeping up with the latest market information, with the highest Total Attractiveness Score (TAS) of 16.24. This study provides strategic recommendations for CV ANDHY KARYA to improve competitiveness and sales volume through product innovation and technology utilization.